(untitled) (Journal of Pathology of Nepal, 2019)
Tuberculosis and leprosy are chronic mycobacterial infections that elicit granulomatous inflammation. The incidence of co-existence of pulmonary tuberculosis and leprosy has ranged from 2.5%-13.4%.1 Cutaneous tuberculosis is a variant of extrapulmonary tuberculosis and its simultaneous occurrence with leprosy is uncommon. The concomitant presence of leprosy, pulmonary as well as cutaneous tuberculosis is rare. We report a case of borderline tuberculoid leprosy, lupus vulgaris and pulmonary tuberculosis in a 45 years male who presented to the dermatology outpatient department with three morphologically distinct skin lesions over the posterior aspect of right leg. Ours is presumably the first case reported from Nepal, a country where both of these mycobacterial infections are endemic.